2013
DOI: 10.1016/j.tvjl.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of dexamethasone after intravenous and intramuscular administration in pigs

Abstract: a b s t r a c tThe pharmacokinetics of dexamethasone (DEX) were investigated after an intravenous (IV) or intramuscular (IM) bolus injection of 0.3 mg/kg bodyweight DEX sodium phosphate in pigs. The plasma concentrations of DEX were determined using a validated high-performance liquid chromatographytandem mass spectrometry (LC-MS/MS) method and the pharmacokinetics were determined by one-compartmental analysis.The mean area under the plasma concentration-time curve and the mean elimination half-life were 133.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…In the present study, bioavailability after oral administration of deflazacort ( F = 87.48%) was high, but this value was lower than to values have been obtained for other glucocorticoids in mammalian species (Wyns et al., ). These results indicate that glucocorticoids show good absorption after extravascular routes of administration.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In the present study, bioavailability after oral administration of deflazacort ( F = 87.48%) was high, but this value was lower than to values have been obtained for other glucocorticoids in mammalian species (Wyns et al., ). These results indicate that glucocorticoids show good absorption after extravascular routes of administration.…”
Section: Discussioncontrasting
confidence: 80%
“…The apparent volume of distribution at steady-state (V ss ) was 4.08 ± 0.31 L/kg, this value indicates that deflazacort is widely distributed into the extravascular tissues. In other studies, larger volumes of distribution (V d ) were described for glucocorticoids in pigs (2.78 L/kg; Wyns et al, 2013) and dogs (5.2-7.7 L/kg; Ryrfeldt, Tonnesson, Nilsson, & Wikby, 1979).…”
Section: Discussionmentioning
confidence: 89%
“…Dexamethasone has been known to improve local anesthetics analgesia under different circumstances. 19,20 In pigs, an intramuscular bolus injection of dexamethasone resulted in a fast and complete absorption and a high absolute bioavailability, 21 which would partly explain the immediate analgesic effect in our population.…”
Section: Vas (Cm)mentioning
confidence: 91%
“…Previous studies in our laboratory have shown that administering a glucocorticoid receptor agonist (GRA) during early weaning can help reduce systemic inflammation and consequently improve post-weaning growth performance in pigs [2,5,6]. Dexamethasone was chosen as the GRA because its anti-inflammatory properties are well studied, it is frequently used in the livestock industry, and its short half-life eliminates the possibility of any residues at slaughter [2,7]. However, the GRA treatment in these studies was delivered via repeated intramuscular (I.M.)…”
Section: Introductionmentioning
confidence: 99%